Research on nano H2/O2 bubble generating mechanism and characteristics - Kuo, Chia-Lung; Chen, Chin-Ta; Ho, Chao-Ching (Frontiers in Chemistry, 2022)
In this research, electrolysis water is used to produce hydrogen and oxygen for carrying out the vertical cutting through high-speed water in order that the bubbles will be refined for generating the nano H2/O2 bubble liquid. In the meantime, a Nanobubble Generator is developed to verify the basic characteristics of the produced nano H2/O2 bubbles. Its purpose is to identify the maximum concentration of bubbles in the nano H2/O2 bubble liquid, the bubble production efficiency and bubble electrification characteristics as well as the effect of reducing the pipe flow friction resistance together with the characteristics of nanobubbles containing varied gases. By verifying the nano H2/O2 bubbles, it is hoped that the flowing rate of the hollow electrode can be elevated.